The property that yields -12+36=x-36+36 is the additive inverse property.
The additive inverse property states that for any real number a, there exists a number -a such that a + (-a) = 0.
In this case, -12 is the additive inverse of 12, since 12 + (-12) = 0. Therefore, we can rewrite the equation as:
-12 + 36 = (x - 36) + 36
Now, we can simplify the equation:
24 = x
So, the solution to the equation is x = 24.
Therefore, the property used was the additive inverse property.
Which property yields -12+36=x-36+36. Additive inverse, additive identity, addiction property commutive property
1 answer